Identification of Phytochemical Compounds and Determination of Flavonoid and Tannin Levels in Wedelia (Sphagneticola trilobata (L.) Pruski) - Setiawan, Haris; Hidayat, Andika Gundawa; Wardani, Diah Kartika; Makhabati, Ulinuha Farah (Universitas Ahmad Dahlan, 2025)
Wedelia plant, which has the scientific name Sphagneticola trilobata (L.) Pruski, is one of the plants classified as weeds and is found in various agricultural areas. The largest phytochemical compound content in wedelia leaves consists of flavonoids, tannins and alkaloids. The purpose of this study was to identify phytochemical compounds contained in wedelia leaves and to determine the levels of existing compounds. This research method consists of wet sorting, making extracts by maceration method using 96% ethanol. The ethanol extract was then analyzed using Fourier Transform InfraRed (FT-IR), High Performance Liquid Chromatography (HPLC), and UV-Vis Spectrophotometer. Data analysis to determine the line equation and correlation value using statistical analysis application SPSS Version 30.0 and analysis of phytochemical compound components using descriptive analysis. Based on the results of the analysis of phytochemical compounds using the FTIR method, several functional groups were obtained that were very identical to antioxidant compounds in the form of flavonoids, tannins, and alkaloids. After that, further tests on flavonoid levels using the HPLC method obtained levels of 215.435 mg/g (%b/b), and determination of tannin levels using a UV-Vis Spectrophotometer obtained levels of 128.35 mg/g (%b/b).